PENGARUH FREE CASH FLOW DAN SALES GROWTH TERHADAP DIVIDEN PAYOUT RATIO - Kelvira Putri Ramdhany; Acep Suherman; Elan Eriswanto (Jurnal Proaksi, 2020)
This research aims to examine the influence of free cash flow and sales growth on dividend payout ratio.. The research method conducted is quantitative with an associative approach, the type of data used is secondary data in the form of financial statements of textile and garment sub-manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2019. The results showed that free cash flow has a negative effect on dividend payout ratio, sales growth has no effect on dividend payout ratio, and free cash flow and sales growth simultaneously affect dividend payout ratio. Keywords : Fre Cash Flow, Sales Growth, Dividend Payout Ratio